The Relationship of Oxygen Saturation With Malaise In Diabetes Mellitus Patients in Jember - Pranata, Andi Eka; Jannah, Nikmatul; Sukowati, Umi (LPPM Universitas dr. Soebandi, 2024)
Introduction: Diabetes mellitus causes sugar in the blood to not be brought into cells and causeshyperglycemia. Excessive levels of sugar in the blood can disrupt the work of blood cells whichwill release oxygen so that oxygen in the blood becomes reduced which causes hypoxia inperipheral tissues. Glucosuria causes the body to lose calories, causing a decrease in metabolicenergy and malaise. This study aimed to analyze the relationship of oxygen saturation withmalaise in diabetes mellitus patients. Methods: The design used in this research is a cross-sectional approach. The population of DM patients at hospital on average in the last 3 monthswas 160 patients. The sample in this study was 50 respondents. This study used a samplingtechnique of no-probability sampling with the Quota sampling method. Data collection in thisstudy used oximetry and the DSS questionnaire. The data analysis technique used is theSpearman test. Results: This study showed that most of the oxygen saturation experiencedmoderate hypoxemia as many as 20 people and the category of acute malaise was 1 person (2%),subacute malaise was 16 people (32%), and chronic malaise was 33 people (66%). Based on theresults of the Rank Spearman statistical test, it is known that there is a relationship betweenoxygen saturation and malaise in diabetes mellitus patients (p-value 0.000 α < 0.05).Conclusion: There is a relationship between oxygen saturation and malaise in Diabetes Mellituspatients. The health care system can implement the comprehensive strategy to solve problemrelated to diabetes mellitus patient.